ANALISIS PENGARUH MATERIAL KEMASAN, TAMPILAN KEMASAN, BENTUK KEMASAN, DAN INFORMASI PADA KEMASAN TERHADAP MINAT BELI MAKANAN KHAS LAMPUNG KERIPIK PISANG - Fitriani, Risa; Nugraha, Andhyka Tyaz (Jurnal Ilmiah Teknik Industri, 2024)
The aim of this research is to investigate the influence of packaging material, packaging appearance, packaging shape, and information on the packaging on consumer purchasing interest in Asa Cipto Roso MSMEs, Siger Keripik MSMEs, and Lampung Chips MSMEs. The method applied in this research is the PLS-SEM method with the help of software in the form of SmartPLS 3.0. Research data was collected from 120 respondents who were banana chips consumers at Asa Cipto Roso MSMEs, Siger Keripik MSMEs, and Lampung Chips MSMEs which were distributed via an online Google form. The findings from this research illustrate that packaging elements which include packaging material, packaging appearance, packaging shape, and information on the packaging can trigger consumer buying interest in Asa Cipto Roso MSMEs, Siger Keripik MSMEs, and Lampung Chips MSMEs. The findings from this research can provide implications for designing banana chip packaging that suits consumer tastes so that it can trigger consumer buying interest in Asa Cipto Roso MSMEs, Siger Keripik MSMEs, and Lampung Chips MSMEs.